Hyperbaric Oxygen Therapy Represses the Warburg Effect and Epithelial–Mesenchymal Transition in Hypoxic NSCLC Cells via the HIF-1α/PFKP Axis - Zhang, Linling; Ke, Jingjing; Min, Shengping; Wu, Nan; Liu, Fei; Qu, Zhen; Li, Wei; Wang, Hongtao; Qian, Zhongqing; Wang, Xiaojing (Frontiers in Oncology, 2021)
Background Tumor cells initiate hypoxia-induced mechanisms to fuel cell proliferation, invasion, and metastasis, largely mediated by low O2-responsive Hypoxia-Inducible Factor 1 Alpha (HIF-1α). Therefore, hyperbaric oxygen therapy (HBO) is now being studied in cancer patients, but its impact upon non-small-cell lung cancer (NSCLC) cell metabolism remains uncharacterized. Methods We employed the NSCLC cell lines A549 and H1299 for in vitro studies. Glucose uptake, pyruvate, lactate, and adenosine triphosphate (ATP) assays were used to assess aerobic glycolysis (Warburg effect). A quantitative glycolytic flux model was used to analyze the flux contributions of HIF-1α-induced glucose metabolism genes. We used a Lewis lung carcinoma (LLC) murine model to measure lung tumorigenesis in C57BL/6J mice. Results HBO suppressed hypoxia-induced HIF-1α expression and downstream HIF-1α signaling in NSCLC cells. One HIF-1α-induced glucose metabolism gene—Phosphofructokinase, Platelet (PFKP)—most profoundly enhanced glycolytic flux under both low- and high-glucose conditions. HBO suppressed hypoxia-induced PFKP transactivation and gene expression via HIF-1α downregulation. HBO’s suppression of the Warburg effect, suppression of hyperproliferation, and suppression of epithelial-to-mesenchymal transition (EMT) in hypoxic NSCLC cell lines is mediated by the HIF-1α/PFKP axis. In vivo, HBO therapy inhibited murine LLC lung tumor growth in a Pfkp-dependent manner. Conclusions HBO’s repression of the Warburg effect, repression of hyperproliferation, and repression of EMT in hypoxic NSCLC cells is dependent upon HIF-1α downregulation. HIF-1α’s target gene PFKP functions as a central mediator of HBO’s effects in hypoxic NSCLC cells and may represent a metabolic vulnerability in NSCLC tumors.